2019
DOI: 10.1177/1046496419853019
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Information Elaboration: The Critical Role of Framing and Initial Dialogue

Abstract: Information elaboration is crucial for successfully responding to change, and teams inevitably frame changes to ground them. Yet, there is sparse knowledge around how framing affects information elaboration. In investigating the relationship that framing has with information elaboration, we show that framing starts a domino effect throughout the phases of information elaboration. Our experiment shows that opportunity framing motivates teams to engage with the change by asking questions about it, which increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 72 publications
(144 reference statements)
0
12
0
Order By: Relevance
“…Because a member withholding unshared information could hurt the team's ability to determine and solve the equations, it should be considered conjunctive when goals are not shared 3 (Barrick et al, 1998). However, Sanner and Evans (2019) recently conducted a detailed analysis of the interactions that take place during this task when goals are shared. They found that shared approaches reliably form in teams, allowing for members to coordinate actions so that they can compensate for each other in developing a shared task understanding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a member withholding unshared information could hurt the team's ability to determine and solve the equations, it should be considered conjunctive when goals are not shared 3 (Barrick et al, 1998). However, Sanner and Evans (2019) recently conducted a detailed analysis of the interactions that take place during this task when goals are shared. They found that shared approaches reliably form in teams, allowing for members to coordinate actions so that they can compensate for each other in developing a shared task understanding.…”
Section: Methodsmentioning
confidence: 99%
“…Interdependence theory suggests that shared goals encourage a member to try to cooperatively compensate for another member, because doing so is in that member's own interest (van der Vegt, van de Vliert, & Oosterhof, 2003). For example, a member not sharing information is frequently compensated for by another member getting the information through asking questions in contexts where teams have shared goals (Sanner & Evans, 2019). In contrast, competitive or independent goals give members little reason to help each other out, creating a conjunctive aggregation of behaviors where one member's unproductive behavior is likely to harm group outcomes.…”
Section: Dyadic and Team Communal Orientationmentioning
confidence: 99%
“…While we attempted to collect data at times that were guided by prior theory and research (Gersick, 1989), it is possible that our conclusions would differ if we had gathered data at more frequent intervals (Mitchell & James, 2001). More continuous measurements could uncover important micro-dynamics (Sanner & Evans, 2019) and changes that we could not detect (McGrath, 1997). Thus, our study highlights the importance of studying informal hierarchy strength changes and encourages the use of dynamic models in future informal hierarchy strength research.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 95%
“…The only empirical paper we were able to find that looked into antecedents of informal hierarchy strength (Oedzes et al, 2019) focused on a fixed feature of most teams, the existence of a formal leader. Pressure, on the other hand, can be influenced by tactics such as framing (Sanner & Evans, 2019) and keeping members informed (Amiot et al, 2006). Therefore, we contribute to informal hierarchy strength research by identifying an antecedent that can be adjusted along with situational demands.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Because individuals can possess a virtually endless array of schemas but have limited human processing capacity, individuals only have a few active schemas at any given time (Lord, Brown, Harvey, & Hall, 2001). When activated, schemas increase the presence of related motives and behaviors (Kernan & Lord, 1990;Sanner & Evans, 2019). Consequently, LSSs will be strongly related to interaction frequency and interpersonal responsibility when they are activated (DeRue, 2011).…”
Section: How and Where Shared Lss Affects Behaviors: The Adaptive Leadership Theory Perspectivementioning
confidence: 99%